Analysis of building on Sloping Ground subjected to Seismic Forces - Islam, Mojahid; Pastariya, Siddharth (International Journal of Advanced Engineering Research and Science, 2020)
In the current scenario appealing architecture along with high rise buildings is not limited to plain terrain but also extended to the hilly terrain keeping in mind the problems aroused and their effects. This paper presents the comparative analysis of various configurations of 15 storied building with to be found on varying slope with different plan and different structural arrangements situated on seismic zone III. This study compares various reinforced concrete models framed and analyzed their response against dynamic loading to identify and struggle the worst possible scenario. The study is carried out for a combination of four different slopes and different building configuration by response spectrum analysis method and various parameters are compared against various constraints and results obtained from various building cases illustrates that the most optimum case is building C1 and C2 for both step back and step back set back configurations.